Nurse role and mechanism of Coriaria nepalensis in abandoned land of Pb-Zn mining area - Yang, Jie; Tang, Hong; Duan, Chang-qun; Wang, Si-chen; Yuan, Xin-qi; Huang, Lv; Li, Lin-yang (Frontiers in Ecology and Evolution, 2023)
Mining activities, while providing a huge material base for human society, have also caused great damage to the ecosystem. A large amount of mine waste is in urgent need of treatment and remediation. Phytoremediation, as a green and low-cost way of mine site restoration, has been researched by a large number of scholars. Ecological restoration, as a suitable alternative to phytoremediation, has also received extensive attention from scholars too. Field survey revealed that a native plant, Coriaria nepalensis, adapted to the abandoned sites of Pb-Zn mines for its adaptability to pollution and extreme habitats and its improvement of the surrounding microenvironment, with its formation of plant communities may contribute to the natural recovery of the abandoned sites of mines. For this reason, the present study was conducted on the nurse plant, C. nepalensis, which was naturally colonized in the abandoned land of the Pb-Zn mine in Mine Town, Huize County. The specific results of the study are as follows: Coriaria nepalensis promotes the stabilization of the soil structure under the canopy, and the local resources of the soil increase and the “fertilizer island” effect appears: (1) Improvement of physical properties: Compared with the herbaceous sample, the soil bulk density of the Coriaria nepalensis is significantly lower than that of the herbaceous sample. (2) Improve soil nutrition: the organic matter, total nitrogen and total phosphorus contents of the inter-root soil of the Coriaria nepalensis in large multi-diversity sites were higher than those of the herbaceous sample sites. (3) Reducing the toxicity of soil heavy metals to plants: although the total amount of heavy metals and the effective state of the Coriaria nepalensis were significantly higher than that of the herbaceous samples, the diversity and biomass of the plants under the Coriaria nepalensis were not affected, but were higher instead, which indicated that the Coriaria nepalensis mitigated the stress and toxicity of the heavy metals to the plants under the canopy, and allowed the plants to colonize and grow under the canopy. (4) Coriaria nepalensis in Pb-Zn mine abandoned sites can regulating soil microbial community structure, thus enabling plant community succession in degraded environments. Ascomycetes, Mycobacteriophages, Ascomycetes, and Stramenophages with higher abundance. (5) Coriaria nepalensis microbial community structure and increases the abundance of functions associated with nitrogen cycling and stress tolerance. There were higher abundances of bacterial functions related to nitrogen fixation, nitrate reduction, nitrogen respiration, nitrate respiration; and higher abundances of stress-tolerant, parthenogenetic anaerobic, biofilm-forming, aerobic, mobile protozoa-containing, and Gram-negative bacteria in the Coriaria nepalensis. In sum: C. nepalensis can have a nurse effect on its sub-canopy plants by improving microhabitat soil properties and regulating soil microbial community structure in abandoned sites of Pb-Zn mines, thus enabling plant community succession in degraded environments.